2009
DOI: 10.5021/ad.2009.21.4.382
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of NMDA Receptor 1 Correlates with Clinicopathological Parameters in Cutaneous Squamous Cell Carcinoma

Abstract: Background: Ionotropic glutamate receptors of the N-methyl-D-aspartate receptor (NMDAR) type are expressed on keratinocytes and play a role in the proliferation, differentiation, and cornification of keratinocytes. However, the expression profile of NMDAR and its role in cutaneous malignancy is unclear. Objective: We analyzed the expression of NMDAR-1 in cutaneous squamous cell carcinoma (SCC) and investigated the relationship between NMDAR-1 expression and clinicopathological parameters. Methods: Thirty-two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Survival analysis demonstrated that upregulated GRINA expression was associated with worse OS in patients with CRC. These results were consistent with previous studies ( 7 , 18 , 19 ). Collectively, these results highlighted the potential role of GRINA in the development and progression of CRC.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Survival analysis demonstrated that upregulated GRINA expression was associated with worse OS in patients with CRC. These results were consistent with previous studies ( 7 , 18 , 19 ). Collectively, these results highlighted the potential role of GRINA in the development and progression of CRC.…”
Section: Discussionsupporting
confidence: 94%
“…Aberrant NMDAR expression has been detected in several types of cancer, including oral squamous cell carcinoma (OSCC), cutaneous squamous cell carcinoma, prostate cancer and GC ( 17 ). NMDAR1 (a glutamate receptor) expression in cutaneous squamous cell carcinoma is significantly associated with cancer metastasis and differentiation ( 18 ). In OSCC, NMDAR1 upregulation is significantly associated with cancer stage, lymph node metastasis and tumor size ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…GluN1 expression in oral squamous cell carcinoma significantly correlated with tumor size, incidence of lymph node metastasis. and cancer stage [140,141], while GluN1 silencing reduced cancer cell proliferation [142]. This suggests that GluN1 expression may predict poor patient outcome.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…GRIN2A and GRIN2B hypermethylation inversely correlated with GluN2A and GluN2B expression levels, and was associated with increased cancer cell proliferation and colony formation in vitro [143,144]. In [129,198] Small-cell GluN1; GluN2A-C [134] Connective tissue (muscle, bone) Sarcoma GluN1; GluN2A-D; GluN3A,B [198] Thyroid Carcinoma GluN1; GluN2B-D; GluN3A,B [198] Plasma cell Multiple myeloma GluN1; GluN2A-D [198] Colon/rectum Adenocarcinoma GluN1; GluN2A-D; GluN3A [129,138,198,199] T cell Leukemia GluN2A-D; GluN3A [198] Breast Adenocarcinoma GluN1; GluN2A-D; GluN3A [126,129,198] Ovaries Cystadenocarcinoma GluN1; GluN2B [202] Endometrioid adenocarcinoma GluN1; GluN2B [202] Clear-cell carcinoma GluN1; GluN2B [202] Megakaryoblasts Leukemic megarkaryoblasts GluN1; GluN2A-D; GluN3A,B [132] Oral cavity Squamous cell carcinoma GluN1 [140,141] Larynx Squamous cell carcinoma GluN1; GluN2A-D; GluN3A [136] Bone Osteosarcoma GluN1; GluN2A,B,D; GluN3A [203] accordance, ectopic GluN2B overexpression induced NMDAR-mediated apoptosis in gastric [144] and esophageal squamous cell carcinoma cells [143], and GluN2A overexpression stimulated colorectal cancer cell death [146]. In addition, whole-exome sequencing in malignant melanoma tumor samples revealed a significant prevalence of clustered mutations within GRIN2A functional domains, leading to truncated GluN2A [147], reduced NMDAR complex formation, and increased cancer cell growth, migration [148], and disease progression [149].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%